MAC for dedicated short range communications in intelligent transport system. - Zhu, Jing (IEEE Communications magazine)
The need for critical improvements to the North American surface transportation infrastructure vis-a-vis alleviation of congestion while enhancing public safety has led to new intelligent transportation system (ITS) infrastructure based on vehicle-to-vehicle (v2v) wireless communications. The allocation of 75 MHz in the 5.9 GHz band for dedicated short-range communications (DSRC) may also enable future delivery of rich media content to vehicles at short to medium ranges via vehicle-to-roadside (v2e) links. Recently, AASTM committee E17.51 endorsed a variant of the IEEE wireless LAN standard, denoted 802.11a roadside applications (R/A), as the platform for the DSRC link and data link layer. In this article, we provide a tutorial overview of DSRC applications and assess IEEE802.11 PHY and MAC layer characteristics in this context. It is anticipated that current 802.11 specifications need to be suitably altered to meet requirements for DSRC environments of multihop connectivity, high vehicle mobility, and heterogeneous services with a variety of QoS requirements for which the original design was not intended. This article captures the current state of the art of 802.11-based multiple access protocols and highlights open research issues.